2022
DOI: 10.3390/ijms23136960
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Attenuates UVA-Induced Skin Photoaging by Suppressing Mitophagy and the PI3K/AKT/mTOR Pathway

Abstract: Ultraviolet (UV) radiation is a major cause of photoaging that can induce DNA damage, oxidative stress, and cellular aging. Metformin (MF) can repair DNA damage, scavenge reactive oxygen species (ROS), and protect cells. However, the mechanism by which MF inhibits cell senescence in chronic skin damage induced by UVA is unclear. In this study, human foreskin fibroblasts (HFFs) treated with UVA were used as an in vitro model and UVA-induced skin photoaging in Kunming mice was used as an in vivo model to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…Ultraviolet radiation can cause DNA damage, which further leads to DNA breakage and mismatch . The PI3K/AKT/NF-κB pathway is crucial for DNA damage repair, cell proliferation, inflammation, and other cellular activities. , The expression of proteins in the PI3K/AKT/NF-κB pathway was examined by western blotting. As shown in Figure A,B, the PI3K, AKT, IκBα, and NF-κB phosphorylation levels were notably enhanced in UVB-irradiated HaCaT cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultraviolet radiation can cause DNA damage, which further leads to DNA breakage and mismatch . The PI3K/AKT/NF-κB pathway is crucial for DNA damage repair, cell proliferation, inflammation, and other cellular activities. , The expression of proteins in the PI3K/AKT/NF-κB pathway was examined by western blotting. As shown in Figure A,B, the PI3K, AKT, IκBα, and NF-κB phosphorylation levels were notably enhanced in UVB-irradiated HaCaT cells.…”
Section: Resultsmentioning
confidence: 99%
“…Considerable evidence has confirmed that the phosphatidylinositol 3-kinase (PI3K)/AKT signaling pathway is one of the most distinctive and crucial pathways that are activated in response to the repair of DNA breakage, inflammation, and other cellular activities after UV exposure. , PI3K regulates keratinocyte proliferation by activating and phosphorylating AKT and its downstream target molecules in human skin . Furthermore, it has been well documented that the activation of AKT results in phosphorylation of NF-κB at residue Ser536 and subsequent activation in skin photoaging .…”
Section: Introductionmentioning
confidence: 99%
“…The biological functions involved in these proteins were evaluated by GO and KEGG enrichment analysis, which showed that differentially expressed proteins involved in SIONFH were signi cantly enriched in certain aspects of autophagy, mitochondria, apoptosis, FOXO signaling pathway and mTOR signaling pathway. The mTOR signaling pathway was found to mediate the regulation of mitochondrial autophagy to play an anti-photoaging role 29 , it also regulates mitochondrial dysfunction in the kidney 30 . FOXO is involved in the regulation of mitochondrial homeostasis, mediates mitochondrial fusion and ssion, and controls mitochondrial autophagy during the autophagy formation and maturation stages 31 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, loss of autophagy or upregulation of mTOR signaling contributes to photoaging (Chen et al, 2022;Lim et al, 2020;Wang et al, 2019). Moreover, mTOR can also suppress SASP production via MAPKAPK2 translation in oncogene-induced senescence (OIS) (Herranz et al, 2015).…”
Section: K E Y S I G Naling Pathways Involved In Dermal Fib Rob L a S...mentioning
confidence: 99%